"If it helps …" the use of microarray technology in prenatal testing: Patient and partners reflections. Issue 7 (21st May 2013) - Hillman, Sarah C.; Skelton, John; Quinlan‐Jones, Elizabeth; Wilson, Amie; Kilby, Mark D.
Abstract The objective was to gain insight into the experiences of women and their partners diagnosed with a fetal abnormality on prenatal ultrasound examination and receiving genetic testing including microarray. Twenty‐five semi‐structured interviews were performed with women +/− their partners after receiving the results of prenatal genetic testing. Framework analysis was performed to elicit themes and subthemes. Five main themes were recognized; diagnosis, genetic testing, family and support, reflections of the treatment received and emotions. Our results showed that women recall being told about QFPCR for trisomy 13, 18, and 21 but often no further testing. Women expected the conventional karyotype and microarray result would be normal following a normal QFPCR result. There were frequent misconceptions by couples regarding aspects of counseling/testing. Communication of variants of unknown (clinical) significance (VOUS) presents a particularly difficult challenge. Good clear communication by health care professionals is paramount. When counseling women and their partners for fetal chromosomal testing it should be reinforced that although the most common, trisomy 13, 18, and 21 only account for some of the chromosomal changes resulting in abnormal scan findings. Couples should have literature to take home summarizing scan anomalies and reinforcing information about genetic testing. © 2013 Wiley Periodicals, Inc.